Educating the Germans : people and policy in the British Zone of Germany, 1945-1949 - Phillips, David 1944- (Bloomsbury Academic, 2020)
Educating the Germans examines the role of the British in the 'reconstruction' of education in occupied Germany from 1945 to 1949. It covers war-time planning for a future role in overseeing education at all levels in Germany, looks at policy and its implementation, describes the personnel involved and their interaction with German authorities, and assesses the lasting effects of the British effort in securing the future development of education from Kindergarten to university in the emerging Federal Republic. Some comparison is made throughout with parallel efforts in the US, French, and Soviet Zones of Occupation. By way of background, there is also a discussion of Nazi education policy and its effects.Thoroughly researched and employing a wide range of sources, this is an important study for anyone looking to further their understanding of Germany, and Britain's relationship with Germany in the postwar era.